Methodological Methods Of Teaching Children For Movement Activities In The Process Of Physical Education Classes - L.A.Azimov; M.A.Ruzimboev (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2021)
The article discusses the methodological methods of teaching children physical activity in the process of physical education and the methodological methods used in teaching children physical activity